Losing control freedom of the press in Asia - Rich, Roland; Williams, Louise 1961- (ANU E Press, 2013)
'A free press is not a luxury. A free press is at the absolute core of equitable development' according to World Bank President James Wolfensohn. A free press is also the key to transparency and good governance and is an indispensable feature of a democracy. So how does Asia rate? In Losing Control, leading journalists analyse the state of play in all the countries of North Asia and Southeast Asia. From the herd journalism of Japan to the Stalinist system of North Korea, Losing Control provides an inside look at journalism and freedom of the press in each country. One conclusion--a combination of new technology and greater democracy is breaking the shackles that once constrained the press in Asia